Changes in the higher education sector contemporary drivers and the pursuit of excellence. - KHAN, KHALID. GURBUTT, DAWNE. CRAGG, RACHEL (Anthem Impact., 2022)
This book considers the essential attributes of excellence in teaching as well as the main current factors both internally and externally that are driving higher educational institutes to raise their quality of teaching. It looks at the latest teaching methodologies that promotes deep learning and enables students to ultimately become independent learners.